2016
DOI: 10.1016/j.wocn.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dialectal differences using articulography

Abstract: The present study introduces articulography, the measurement of the position of tongue and lips during speech, as a promising method to the study of dialect variation. By using generalized additive modeling to analyze articulatory trajectories, we are able to reliably detect aggregate group differences, while simultaneously taking into account the individual variation across dozens of speakers. Our results on the basis of Dutch dialect data show clear differences between the southern and the northern dialect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 56 publications
1
69
0
Order By: Relevance
“…Furthermore, a single-segment study is unsuitable to shed light on differences in articulatory settings, as differences in articulation of the specific segment and articulatory setting differences cannot be distinguished. Interestingly, Wieling et al (2015) and Wieling et al (2016) conducted an articulatory analysis of the tongue movement data associated with the word pronunciations (as opposed to the data associated with the pauses analyzed in this study) of the experiment explained above, and found a similar pattern as reported in the present study, with a more posterior tongue position for the speakers from Ter Apel compared to those from Ubbergen. This suggests that articulatory setting differences may also be observed when analyzing a sizeable amount of variable speech data (i.e., not only focusing on a single segment).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, a single-segment study is unsuitable to shed light on differences in articulatory settings, as differences in articulation of the specific segment and articulatory setting differences cannot be distinguished. Interestingly, Wieling et al (2015) and Wieling et al (2016) conducted an articulatory analysis of the tongue movement data associated with the word pronunciations (as opposed to the data associated with the pauses analyzed in this study) of the experiment explained above, and found a similar pattern as reported in the present study, with a more posterior tongue position for the speakers from Ter Apel compared to those from Ubbergen. This suggests that articulatory setting differences may also be observed when analyzing a sizeable amount of variable speech data (i.e., not only focusing on a single segment).…”
Section: Discussionsupporting
confidence: 73%
“…The experiment consisted of first naming 70 images (e.g., the image of a sheep, pronounced by the participant as an individual word "sheep") in their local dialect, and subsequently reading 27 consonant-vowel-consonant (CVC) sequences (C: /t,k,p/, V: /a,i,o/) from a computer screen in standard Dutch (see Wieling et al, 2015). Both parts were repeated twice, and the items within each repetition were ordered randomly.…”
Section: Articulatory Data Collectionmentioning
confidence: 99%
“…This, also, reduces co-linearity between the global smoother and the group-specific terms which occasionally leads to high uncertainty around the global smoother (see section V for more details). TPRS with m=1 have a more restricted null space than m=2 smoothers, so should not be as collinear with the global smoother (Wieling et al, 2016;Baayen et al, 2018). We have observed that this is much more of an issue when fitting model 3 compared to model 2.…”
Section: A Single Common Smoother Plus Group-level Smoothers With Difmentioning
confidence: 92%
“…Introductions to GAMs focusing specifically on application to phonetics are Wieling et al (2016); Baayen and Linke (2019). Wieling et al (2016) used GAMs to analyze tongue movement data obtained with electromagnetic articulography, investigating the difference in articulatory trajectories between two Dutch dialects. Baayen and Linke (2019) analyzed the distribution and occurrence of pronunciation variants, extracted from the Buckeye corpus, with GAMs.…”
Section: Further Referencesmentioning
confidence: 99%